Air‐Stable Solar Cells with 0.7 V Open‐Circuit Voltage Using Selenized Antimony Sulfide Absorbers Prepared by Hydrazine‐Free Solution Method (Solar RRL 5∕2019). Issue 5 (3rd May 2019) - Cheng, Jiang; Hu, Rong; Wang, Kun; Meng, Xiang; Li, Ying; Yang, Xin; Liao, Xiaoqing; Li, Lu; Chong, Kok Boon
Abstract : In article no.1800346, Lu Li, Kok Boon Chong, and co‐workers introduce a novel method to fabricate a high‐VOC Sb2 (S1‐x Sex )3 thin film solar cell via spray pyrolysis deposition. They achieve a high power conversion efficiency of 4.57% for spray coated devices and prepare a 8 × 8 cm 2 large‐scale module with a power conversion efficiency of 3.19%, suggesting this technique is promising for industrial application.